A horizontally polarized end‐fire antenna with complete ground for 5G mmWave applications. Issue 12 (7th August 2020) - Liu, Ying; Zhao, Chang; Yue, Zhenzhen; Ren, Aidi; Jia, Yongtao
Abstract: A novel design of horizontally polarized end‐fire antenna array with a complete ground (GND) for the fifth‐generation (5G) millimeter wave (mmWave) applications is proposed in this article. The antenna employs four dielectric layers with the relative permittivity successively increasing from top to bottom. Utilizing the refraction of the radiated waves between different dielectric layers, the uptilting of the beam in the end‐fire direction caused by the complete GND has been solved. A pair of butterfly dipole is fed by a balun to produce horizontal polarization. The simulated result shows that the proposed antenna unit achieves a fractional impedance bandwidth of 19.6% (24.25‐29.5 GHz) with the gain varying from 4.3 to 6.51 dBi. Based on the antenna element, a 1 × 4 antenna array is proposed. The isolation of the array is 17.6 dB. Besides, the end‐fire gain is 7.51 to 10.2 dBi over the frequency band of 24.25 to 29.5 GHz. And the beam scanning range of the array covers from −54° to +54°. A prototype is fabricated and measured, which validates the simulated results. Both the simulation and experiment results prove that the proposed antenna is promising for 5G mmWave applications.